2023
DOI: 10.1007/s40519-023-01625-5
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide 3.0 mg and mental health: can psychiatric symptoms be associated to adherence to therapy? Insights from a clinical audit

Silvia Tempia Valenta,
Michele Stecchi,
Federica Perazza
et al.

Abstract: Introduction Liraglutide 3.0 mg, a glucagon-like peptide-1 (GLP-1) analogue, is a medication approved for obesity treatment. This study aimed to investigate the relationship between psychiatric symptoms, including depression, anxiety, and binge eating, and their impact on therapy adherence. Methods A clinical audit was carried out on a cohort of 54 adults with obesity treated with liraglutide 3.0 mg. We retrospectively analyzed the connection betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The prescription of anti-obesity pharmacotherapy is not reimbursed by the Italian healthcare system, and the high cost represents one of the main barriers to treatment, as not all patients are able to afford it. In some real-world studies, patient payment for obesity medications has been identified as a cause of higher discontinuation rates [12]. In this study, during data collection, the patient's visit date, prescribed dose, and number of liraglutide prescriptions were reviewed to determine whether the medication had been discontinued.…”
Section: Data Collection and Definitionmentioning
confidence: 99%
“…The prescription of anti-obesity pharmacotherapy is not reimbursed by the Italian healthcare system, and the high cost represents one of the main barriers to treatment, as not all patients are able to afford it. In some real-world studies, patient payment for obesity medications has been identified as a cause of higher discontinuation rates [12]. In this study, during data collection, the patient's visit date, prescribed dose, and number of liraglutide prescriptions were reviewed to determine whether the medication had been discontinued.…”
Section: Data Collection and Definitionmentioning
confidence: 99%
“…The prescription of anti-obesity pharmacotherapy is not reimbursed by the Italian healthcare system, and the high cost represents one of the main barriers to treatment, as not all patients are able to afford it. In some real-world studies, patient payment for obesity medications has been identified as a cause of higher discontinuation rates [12]. In this study, during data collection, the patient's visit date, prescribed dose, number of liraglutide prescriptions, any adverse effects, and whether these effects led to discontinuation of the medication were reviewed to determine whether the medication had been discontinued.…”
Section: Data Collection and Definitionmentioning
confidence: 99%
“…[ 4 ] There were reports of increased suicidal ideation with the use of Liraglutide; however, a recent systematic review by the European Medicines Agency stated that there is no causal relationship between GLP-1RAs and suicide. [ 5 ] Further more, studies suggest potential antidepressant effects of GLP-1RAs, [ 6 8 ] which may be related to their involvement in the regulation of inflammation [ 9 , 10 ] and hormones such as cortisol and thyroid hormones. [ 11 ] Here, we report a case of a young male who developed depressive symptoms after using Liraglutide for blood sugar control and weight reduction.…”
Section: Introductionmentioning
confidence: 99%